Topographical and vegetational characteristics of lynx kill sites in Slovenian Dinaric mountains - Krofel, Miha (Natura Sloveniae, 2007)
We report on topographical and vegetational characteristics of 13 sites where Eurasian lynx (Lynx lynx killed its prey in the Dinaric mountain range in Slovenia. The results suggest that lynx does not necessarily need dense vegetation and rugged terrain to successfully hunt its prey, however, it may influence its hunting success. A large part of the successful hunts took placeon steep slopes and rugged terrain. 39% of kill sites were located in dolines, implying the potential importance of these karst structures for the hunting of large carnivores on ungulates in karst areas such as Dinaric Mountains.
Keywords: Behavior, Animal; Carnivora; Dinaridi; Ecosystem; Ekosistem; Mesojedi; mesta uplenitev; predacija; Predatorsko vedenje; Predatory Behavior; risi; Slovenia; Slovenija; Vedenje živali; zoologija; zoology